Transformasi fungsi catus patha sebagai lanskap sejarah di Kota Denpasar - Aryawan, Putri Saraswati; Kohdrata, Naniek; Bawono, Rochtri Agung (Jurnal Arsitektur Lansekap, 2019)
Transformation of catus patha functions as historic landscape in Denpasar city. Denpasar city as the Capital of the province, is the center of development in Bali. The former Denpasar city began as a Puri named Puri Denpasar. The location of Puri Denpasar which is the center of government of the Badung Kingdom is in Catus Patha, where the formation of Denpasar city began. This article examine the changes and functions of Catus Patha Denpasar which developed during the Badung Kingdom until now when Denpasar entered the globalization era. The writing method used is only study from various literature sources related to development of the Catus Patha Denpasar. The results of this study are the application of the catus patha concept during the kingdom era can be said to be the most disciplined while it compared to the next periods. In the kingdom era, philosophical values and functions were still original. Entering the colonial era, the elements of the Catus Patha Denpasar is influence by culture brought from Netherlands. Then entering the globalization era, the Catus Patha concept is lies in its elements which also influence its function. The large number of mixed settlements and catur muka statues indicate that the catus patha concept is not well realized in Denpasar.